Enhancement of The Sensitivity of The Refractive Index Sensor Based on D-shaped Coreless Fiber - Dina N. Abdullah; Hanan J. Taher (Iraqi Journal of Laser, 2024)
A refractive index sensor has been developed using a D-shaped coreless fiber (DSCF) sensor technique. This sensor comprises a segment of coreless fiber (CF) spliced between two single-mode fibers (SMFs). The middle of the CF length was polished using a grinding wheel to reduce the diameter on one side, creating a D-shaped cross-sectional profile. The DSCF sensor's performance was tested using different concentrations of sodium chloride (NaCl) solutions, with refractive indices (RI) ranging from 1.33 to 1.38. The optimal polishing depth (PD) of 31 μm was determined experimentally, and this was achieved by extending the polishing duration using a grinding wheel. This led to a sensitivity increase from 70.2nm/RIU to 98nm/RIU, meaning the sensitivity increased by 1.4 times. The DSCF sensor is a high-performance, versatile, and cost-effective device with strong interference ability, suitable for various applications.